Effects of Rational Emotive Behaviour Therapy and Positive Self-Talk on outcomes of Kicks from Penalty Mark among University Football Players in Southwest Nigeria - Oluwafemi Paul Olaoye; Andrew Olu Fadoju; Folasade Racheal Airebamen; Atolani Bose Duyilemi (Athens Journal of Sports, 2026)
Kicks from penalty mark are tie breakers, used in football matches where a winner must emerge. Reports have shown that many university football players have the belief that the outcomes of kicks from penalty mark are based on luck rather than skills. Previous studies have focused more on physiological factors, influencing positive kicks from penalty mark, than on psychological interventions. Therefore, the study was carried out to determine the effects of REBT and PSt on outcomes of kicks from penalty mark among university football players in Southwest Nigeria. A pretest-posttest control group quasi-experimental design, with a 3x3x2 factorial matrix was used. Multistage sampling procedure was adopted. Participants were drawn from first generation federal universities in Southwest Nigeria. Shortened General Attitude and belief Scale (=0.76) was used to screen and select participants in the team list of male football players. The universities were randomly assigned to REBT (11), PSt (11) and Control (11) groups. The instruments used were Belief in Penalty Kicks Outcome Questionnaire (=0.82), Penalty Shooting Skill Test (=0.89) and intervention guides. The data were analyzed, using descriptive statistics, Analysis of covariance, Estimation and Scheffe post hoc at 0.05 level of significance. There was a significant main effect of treatment on outcomes of kicks from penalty mark among the players (F(2; 33) =7.23; partialη2=0.49). The participants in the REBT group had the highest post mean score (7.26), followed by those in PSt (5.45) and control (3.47) groups. There was a significant interaction effect of treatment and playing experience (F(2; 33) =5.15; partialη2=0.41). The players with long playing experience in REBT group had a higher mean score (5.74) than those with short playing experience (4.90). Rational Emotive Behaviour Therapy improved kicks from penalty mark than Positive Self-talk among the participants. Therefore, these therapies should be used as psychological interventions for football players for better outcomes of kicks from penalty mark. Keywords: Rational emotive behaviour therapy, Positive self-talk, Kicks from penalty mark, University football players